RETRACTED ARTICLE: Effects of bilateral Pecto-intercostal Fascial Block for perioperative pain management in patients undergoing open cardiac surgery: a prospective randomized study - Yang Zhang; Haixia Gong; Biming Zhan; Shibiao Chen (BMC Anesthesiology)
Abstract Background Open cardiac surgical patients may experience severe acute poststernotomy pain. The ultrasound-guided Pecto-intercostal Fascial Block (PIFB) can cover anterior branches of intercostal nerves from T2 to T6. The aim of this study was to investigate the effect of bilateral PIFB in patients undergoing open cardiac surgery. Methods A group of 108 patients were randomly allocated to either receive bilateral PIFB (PIFB group) or no nerve block (SALI group). The primary endpoint was postoperative pain. The secondary outcome measures included intraoperative and postoperative sufentanil and parecoxib consumption, time to extubation, time to first feces, length of stay in the ICU and the length of hospital stay. Insulin, glucose, insulin resistance and interleukin (IL)-6 at 1, 2, 3 days after surgery were mearsured. The homeostasis model assessment (HOMA-IR) was used to measure perioperative insulin resistance. Results The PIFB group reported significantly less sufentanil and parecoxib consumption than the SALI group. Compared to the PIFB group, the SALI group had higher Numerical Rating Scale (NRS) pain scores at 24 h after operation both at rest and during coughing. The time to extubation, length of stay in the ICU and length of hospital stay were significantly decreased in the PIFB group compared with the SALI group. The PIFB group had a lower insulin, glucose, IL-6, HOMA-IR level than the SALI group 3 days after surgery. Conclusion Bilateral PIFB provides effective analgesia and accelerates recovery in patients undergoing open cardiac surgery. Trial registration This study was registered in the Chinese Clinical Trial Registry ( ChiCTR 2000030609 ) on 08/03/2020.